1998
DOI: 10.1136/hrt.80.2.141
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal vascular responses in human chronic cardiac failure are both endothelium dependent and endothelium independent

Abstract: Objective-To study underlying vascular responses in chronic heart failure in patients without ACE inhibitor treatment, and to compare them with age matched controls. Design-Forearm blood flow was studied using venous occlusion plethysmography in patients with chronic heart failure (n = 12) and matched controls (n = 13), after infusion of L-NMMA (a nitric oxide synthase inhibitor), glyceryl trinitrate (an endothelium independent vasodilator), and serotonin (an endothelium dependent vasodilator). Results-L-NMMA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 40 publications
3
42
0
Order By: Relevance
“…27,43 The present and previous 10,44 findings show that local heatinginduced cutaneous vasodilation is attenuated in patients with CHF. These observations are consent with those of others showing that patients with CHF exhibit attenuated endothelium-dependent vasodilation of the peripheral circulation, 38,45,46 including skin. 47 However, it is recognized that the present results do not permit the discrimination between altered responsiveness to vasodilator agents, such as nitric oxide, from possible structural changes in the cutaneous vasculature with CHF, previously shown in these patients.…”
Section: Cui Et Al Thermal Regulatory Responses In Chf 2289supporting
confidence: 91%
“…27,43 The present and previous 10,44 findings show that local heatinginduced cutaneous vasodilation is attenuated in patients with CHF. These observations are consent with those of others showing that patients with CHF exhibit attenuated endothelium-dependent vasodilation of the peripheral circulation, 38,45,46 including skin. 47 However, it is recognized that the present results do not permit the discrimination between altered responsiveness to vasodilator agents, such as nitric oxide, from possible structural changes in the cutaneous vasculature with CHF, previously shown in these patients.…”
Section: Cui Et Al Thermal Regulatory Responses In Chf 2289supporting
confidence: 91%
“…Studies to establish whether basal nitric oxide (NO) production is altered in HF patients have yielded conflicting results. [28][29][30][31][32] One study by Maguire et al 33 supports previous observations that NO does not contribute to basal vascular tone in patients with HF. It has been suggested that endothelial damage could result in a reduction in the availability of endothelium-derived NO from either decreased production or increased breakdown.…”
Section: Endothelial Dysfunctionsupporting
confidence: 68%
“…33,50 Some evidence suggests that over time arterial compliance decreases. 51,52 Abnormal smooth muscle function may result from altered responsiveness or impaired diffusion of NO through the arterial wall.…”
Section: Vascular Smooth Muscle Abnormalitiesmentioning
confidence: 99%
“…There is evidence that vascular smooth muscle sensitivity to NO is reduced in diabetes (Maguire et al, 1998). Therefore, we evaluated endothelial-independent relaxation in rat coronary arteries by analyzing concentration responses to the NO donor SNP.…”
Section: Simvastatin Improves Coronary Endothelial Dysfunction 389mentioning
confidence: 99%